Physicochemical and antioxidant properties of stingless bee honey and its effect on cognitive function in mice - Zulkifli, Fairuz Nabila (2018)
Kelulut honey is a local stingless bee honey in Malaysia and has been consumed due to its therapeutic value and high antioxidant content. The antioxidant in honey will helps in giving memory-enhancing effects and improving brain function. However, reports on nootropic effect of this stingless bee honey are still unclear. Therefore, this study aims to investigate the physicochemical and antioxidant constituents of local-harvested stingless bee honey and their effect to spatial learning and memory performance after supplementation to mice. In this study, the physicochemical and antioxidant content of seven stingless bee honey samples (Pasir Mas, Kelantan) were analysed using various spectrophotometric assay and high performance liquid chromatography method. For behaviour study, female Swiss albino mice (N=35) were divided into five groups that consist of four honey-treated groups (n=28) and one untreated control group (n=7). The acute (7 days) and semi-chronic (35 days) honey-treated group mice were supplemented with two dosages of honey (750 mg/kg and 2000 mg/kg) daily via oral gavage. After the treatment period (7 days and 35 days), the mice were then tested with open field test to measure their locomotor activity. Then, they were tested with Morris water maze (MWM) behavioural task to evaluate for their spatial learning and memory performance. Results for physicochemical and antioxidant analysis showed that the highest antioxidant content was detected from Ita-7-TS sample with 57.38 ± 0.24% anti-radical activity; 853.958 ± 150.04 mg GAE/kg honey of total phenolic content; and 1245.00 ± 204.63 mg of quercetin equivalent/kg honey of total flavonoid content. In the MWM test results, the honey-treated group mice showed a decreased in escape latency during acquisition testing. In probe trial test, results showed that all the honey-fed mice group had significant visit (p =.008) and spent more time (p =.000) in the previous platform quadrant as compared to control group, indicating a significant improvement in reference memory. Both semi-chronic treated mice also shown better performance than acute treated mice in dose dependent manner. The high antioxidant potential of the analysed stingless bee honey samples are due to its polyphenols content such as phenolic acid and flavonoid. This polyphenols are phytochemical compounds that give scavenging activities and can activate antioxidant defend system in the brain, hence providing nootropic and neuroprotective effects against brain oxidative stress and tissue damage. This will results in improvements of cognitive function including promoting learning and memory by modulating synaptic plasticity through synaptogenesis. Therefore, the positively significant results from this study, especially on reference memory may suggest that this stingless bee honey supplementation can increase the learning and memory performance in mice, possibly due to its high antioxidant content.